STUDI ATAS KONSEP GENDER DALAM ISLAM - Muhamad Basyrul Muvid muvid (Musawa: Journal for Gender Studies, 2022)
Gender has become a hotly debated topic in this millennial era by people who have created many protest movements, one of which is the "Women Rights" movement which often occurs at home and abroad. The purpose of writing this article is to find out the concept of gender as a whole in the view of Islamic theology. The method used in writing this journal is to use the literature study method by collecting various reference sources from books, journals and various documents related to the concept of gender in Islam. The findings from the study of the concept of gender in Islam are that there is a lot of discrimination between genders that causes divisions so that the concept of gender itself becomes a lively debate. The second finding is the existence of gender equity and gender equality which talk a lot about equality and differences theoretically and historically in a particular case from time to time. Islamic teachings actually glorify the position of women, and have also been interpreted by the Ministry of Religion of the Republic of Indonesia that men are only referred to as "leaders" which means protectors and providers.